Tibial diaphyseal fractures in children: indications and limitations of the treatment with monolateral and hybrid external fixator - Michele Bisaccia; Giuseppe Rinonapoli; Salvatore Di Giacinto; Andrea Schiavone; Simone Lazzeri; David Gomez-Garrido; Juan Antonio Herrera-Molpeceres; Umberto Ripani; Cristina Ibáñez-Vicente; Giuseppe Rollo; Enrico Maria Bonura; Raffaele Franzese; et al. (Medicinski glasnik, 2020)
Aim: To report our indications and limitations about the use of external fixation in children. Methods: It was retrospectively reviewed all tibial fractures treated with monolateral and hybrid external fixator, at our three Centres. It was included 32 fractures which did not show an acceptable reduction after an attempt under anaesthesia. The exclusion criteria were: open fractures, children with previous fractures of the lower limbs, with skeletal congenital diseases, fractures involving the physis and with neurovascular involvement. All fractures were classified according to the AO (Arbeitsgemeinschaft für Osteosynthesefragen) classification. An outcome was evaluated according to the time needed to obtain radiographic bone healing, the range of motion (ROM) of the ankle, the asymmetry of the lower limbs, the malunion, and complications. Results: The average time of consolidation was 10.66 weeks (6-17 weeks). There were no cases of deep infection, but only seven cases of superficial pin infections. No patients reported loss of ROM of the knee or ankle. We had zero cases of residual angle greater than 5°, and in all cases the difference in length between the limbs was ˂1 cm. Conclusion: The external fixation is a viable technique in the treatment of tibial fractures in children. Therefore, the external fixation, both monolateral and hybrid, should be considered a viable treatment for this type of fracture.
Keywords: bone fixation; paediatric; tibia fractures; trauma